2008
DOI: 10.1152/ajpgi.00055.2008
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine release by human colon cancer cells mediates autocrine stimulation of cell proliferation

Abstract: Most colon cancers overexpress M 3 muscarinic receptors (M3R), and post-M3R signaling stimulates human colon cancer cell proliferation. Acetylcholine (ACh), a muscarinic receptor ligand traditionally regarded as a neurotransmitter, may be produced by nonneuronal cells. We hypothesized that ACh release by human colon cancer cells results in autocrine stimulation of proliferation. H508 human colon cancer cells, which have robust M3R expression, were used to examine effects of muscarinic receptor antagonists, ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
130
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 25 publications
3
130
1
Order By: Relevance
“…Considering that in the microenvironment of prostate cancer, the concentration of acetylcholine in prostate cancer tissues may be even higher than the acetylcholine secreted into the medium due to higher cell density, such autocrine acetylcholine signaling likely functions in the prostate in vivo. Further support for our autocrine cholinergic signaling model also comes from the results reported previously in other tissue adenocarcinoma cells, such as colon cancer cells and small-cell lung cancer cells (7,8).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Considering that in the microenvironment of prostate cancer, the concentration of acetylcholine in prostate cancer tissues may be even higher than the acetylcholine secreted into the medium due to higher cell density, such autocrine acetylcholine signaling likely functions in the prostate in vivo. Further support for our autocrine cholinergic signaling model also comes from the results reported previously in other tissue adenocarcinoma cells, such as colon cancer cells and small-cell lung cancer cells (7,8).…”
Section: Discussionsupporting
confidence: 85%
“…In the 1990s, muscarinic receptor subtypes were firstly defined as conditional oncogenes when they were activated by acetylcholine in NIH-3T3 cells (6). Subsequently, muscarinic receptors have been implicated to be involved in a few types of epithelial cancers, including colorectal cancer and small-cell lung cancer (7,8). In addition, activation of muscarinic receptors was reported to promote prostate cancer cell proliferation in vitro (9).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It is well established that ACh is an important neurotransmitter in the central and peripheral nervous systems and acts via activation of ACh receptors (AChRs).Recently, it has been found that ACh is also widely synthesized by a variety of non-neuronal cell types including airway epithelial cells, 5,6 keratinocytes, 7 small and large intestine, gall bladder, 8 glial, 9 vascular endothelial, 10 immune cells and most common cancer cells such as NSCLC, SCLC, colon, glial and ovarian carcinomas. [11][12][13][14][15][16] Although the primary function has not yet been completely elucidated, the expression of ACh in many different cell types suggests that its roles will be fundamental and will present novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…ACh is also found in cancer cells such as small cell lung carcinoma (SCLC) (6), non-small cell lung carcinoma (7), and colon cancer (8). In cell lines of these particular cancers, expression of mAChRs, nAChRs, choline acetyltransferase (ChAT) that synthesizes ACh, and acetylcholine esterase (AChE) that degrades ACh to choline and acetic acid (1,9,10) indicate that ACh is locally synthesized and metabolized.…”
Section: Introductionmentioning
confidence: 99%